Energy audit for laboratory in FKE [electronic resource] - 533970 Khairulanwar Othman; Faridah Hussin, supervisor (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011